2017
DOI: 10.1177/2381336917719684
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Children’s Use of Language During Play in Rural Northern Canadian Kindergarten Classrooms

Abstract: This article reports on research examining the social purposes of Indigenous kindergarten children's language and their construction of Indigenous cultural knowledge within and through interactions with peers during dramatic play and play with construction materials. The participants are three teachers and 29 children from two rural northern Canadian Indigenous communities that are accessible only by plane and winter roads. Data sources are video-recordings of the children's play interactions taken over 4 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
3
0
5
Order By: Relevance
“…Additional barriers to accessing ECEC may be organizational in nature, such as a lack of parental awareness of programs and services (Charlton et al, 2017, Graham & Underwood, 2012, logistical challenges (Graham & Underwood, 2012, Scotland, 2017, gaps in services such as the unequal supply-demand in care availability (Japel & Friendly, 2019), or a lack of culturally relevant programming (Charlton et al, 2017, Graham & Underwood, 2012, Kirova et al, 2013. For example, research has previously reported that the continued focus of Eurocentric curriculum and pedagogy continues to marginalize Indigenous knowledge, culture and languages in Canada (Eisazadeh et al, 2017, Preston et al, 2012, suggesting that some programs and educators view differences in culture as a deficit rather than an asset in early education settings (Kirova, 2013). Culturally relevant programming in early childhood is essential to meet the needs of all children, especially as there is often a cultural imbalance between educators (often White, middle-class, monolingual women) and the population of children (Allen et al, 2017, Saluja et al, 2002.…”
Section: Barriers To Ececmentioning
confidence: 99%
“…Additional barriers to accessing ECEC may be organizational in nature, such as a lack of parental awareness of programs and services (Charlton et al, 2017, Graham & Underwood, 2012, logistical challenges (Graham & Underwood, 2012, Scotland, 2017, gaps in services such as the unequal supply-demand in care availability (Japel & Friendly, 2019), or a lack of culturally relevant programming (Charlton et al, 2017, Graham & Underwood, 2012, Kirova et al, 2013. For example, research has previously reported that the continued focus of Eurocentric curriculum and pedagogy continues to marginalize Indigenous knowledge, culture and languages in Canada (Eisazadeh et al, 2017, Preston et al, 2012, suggesting that some programs and educators view differences in culture as a deficit rather than an asset in early education settings (Kirova, 2013). Culturally relevant programming in early childhood is essential to meet the needs of all children, especially as there is often a cultural imbalance between educators (often White, middle-class, monolingual women) and the population of children (Allen et al, 2017, Saluja et al, 2002.…”
Section: Barriers To Ececmentioning
confidence: 99%
“…To address the third research question, we then used categories derived in our previous research (Eisazadeh et al, 2017;Peterson, 2017) to analyze the social purposes of each mediated action unit: Table 3 provides examples from the data for each of the codes within these social purpose categories.…”
Section: Transcribing and Data Analysismentioning
confidence: 99%
“…The overall goal of the project is to support the language learning and writing of young children. In previous branches of our research, we reported only on children’s use of language to achieve intended purposes in their play (Eisazadeh et al, 2017; Peterson, 2017). Through our ongoing attention to children’s play interactions and our introduction to the growing body of literature on multimodality (e.g.…”
mentioning
confidence: 99%
“…Entre 4 et 6 ans, les enfants vont davantage s'adonner au jeu symbolique plutôt qu'à une autre forme de jeu (Bodovra et Leong, 2012). En jouant, les enfants autochtones s'approprient le langage pour plusieurs fonctions, notamment pour apprendre, pour s'imaginer et pour exprimer un événement réel de leur quotidien (Eisazadeh, Rajendram, Portier et Peterson, 2017). De plus, dans ce contexte, ils élaborent des scénarios de jeu autour d'activités culturelles et significatives pour eux (ex.…”
Section: Problématiqueunclassified
“…De plus, dans ce contexte, ils élaborent des scénarios de jeu autour d'activités culturelles et significatives pour eux (ex. : chasse, pêche, maison) leur permettant de construire un système de signifiants de leur culture autochtone (Eisazadeh et al, 2017). D'ailleurs, à travers le jeu, les enfants construisent leur compréhension de leur culture et s'appréhendent le monde adulte, autant dans les espaces publics, les classes et d'autres réseaux sociaux (Juster et Leichter-Saxby, 2014).…”
Section: Problématiqueunclassified